What are the consequences of initiative-taking in multinational subsidiaries? - Ambos, Tina C; Andersson, Ulf; Birkinshaw, Julian (Journal of International Business Studies, 2010)
The phenomenon of subsidiary initiative has received increasing attention in recent years, but the consequences of initiatives and the associated dynamics of headquarters–subsidiary relationships have received much less research attention. Building on resource dependence theory and self-determination theory we argue that two basic goals subsidiary managers pursue are to achieve autonomy vis-à-vis corporate headquarters, and influence over other units. We investigate how a subsidiary's past initiatives contribute to its bargaining power, and how headquarters’ response – through granting attention or monitoring – affects the realization of the subsidiary's goals. Using structural equation modeling, our hypotheses are tested by drawing on a sample of 257 subsidiaries located in three different countries (Australia, Canada and the United Kingdom). Our results show that subsidiaries are not able to increase their influence through initiatives unless they get headquarters’ attention. We also find that subsidiary initiatives have a direct effect on subsidiary autonomy, but the caveat is that initiatives also evoke headquarters monitoring, which in turn decreases the subsidiary's autonomy. In addition to providing insights into how subsidiaries can achieve their goals, the paper also sheds light on the critical role headquarters plays in leveraging initiatives, and the influence of individual subsidiaries in the multinational enterprise.